Assessing the Impact of Terra Preta from Rice Husk on Soil, Rice Plant Growth, and Yield in the System of Rice Intensification (SRI) - Adrinal, Adrinal; Gusmini; Putri, Elsa Lolita; Kasim, Musliar; Aprilia Herman, Violin Enghel (UNIVERSITY OF LAMPUNG, 2025)
The practice of intensive rice field cultivation and excessive chemical fertilizer use often leads to gradual declines in soil quality and fertility, as well as environmental pollution. By employing Tetadi as an ameliorant technology and adopting SRI cultivation techniques, we can mitigate the adverse effects on rice fields. This study aimed to examine the effects of Tetadi soil ameliorant on the physical properties of paddy soil, growth, and rice yield using the SRI method. The experiments were conducted in paddy fields in Pasar Ambacang, Kuranji, Padang city. Tetadi soil ameliorant was applied at A=0, B=5, C=10, D=15, and E=20 t ha-1. Data on soil physical properties and plants were statistically analysed using ANOVA. The results showed that the change has an insignificant impact on soil physical properties, yet decreases BD (Bulk Density) by 28.2%; increases SOM (Soil Organic Matter) by 18.55%; TPS (Total Pore Space) by 13.7%, moisture content by 5.6%, permeability by 34.2%, and Available Water Pores (AWT) by 20%—application of 20 Mg ha-1. Tetadi increased the number of productive saplings by 52.65% and yield by 69.46% compared to the treatment without Tetadi application.